Improvements in thermoregulation in adverse environmental conditions using a new cooling vest - Vaz Pardal, C.; Ruiz Verdeja, C. (Archivos de medicina del deporte, 2008)
In Qingdao, the sailing venue during the 2008 Olympic Games, it was difficult to control thermal stress after physical exercise due to the extreme environmental conditions. Some of the physiological mechanisms to reduce core temperature such as radiation, convection or conduction become inefficient at air temperatures over 30 degrees Celsius. The heat produced during exercise can only be dissipated by sweat evaporation, but in Qingdao, due to the elevated relative humidity (>80%), this mechanism become less efficient with a negative impact on sailors` performance. Material and methods: The Spanish Olympic sailors acquired a new model of cooling vest (Cryovest ® ) to face the climatic conditions by reducing the core temperature. Radiotelemeter temperature sensors were used, together with an infrared camera in order to verify the effectiveness of this vest. Results: This vest was found to offer the following advantages with respect to existing ones: - Lower reduction of the skin temperature in contact with the vest - More pleasant sensation for the sailor: the temperature of the skin in contact with the vest remains at a stable temperature (15-17ºC), for more than 100 minutes measured using an infrared camera, compared to the drastic temperature reduction in the case of other vests, nearly 5ºC (Figures 1 and 2). - Longer duration of the effects: The outside surface of the vest has three insulating tissues (teflon, aluminum and a thermal insulator) that prolong the duration of its cooling properties for more than two hours, as opposed to the 30 minutes of other vests. - More effective reduction of the core temperature, never exceeding 39,8 degrees Celsius (Figure 3). Conclusions: The french vest at the moment offers advantages with respect to the use of other existing cooling vests. The Spanish Sailing Olympic Team was therefore able to better adapt to the climatic conditions during the Olympic Games.